The Practice of Skilled Nurses in the Care of Patients Diabetes Mellitus: Scoping Review - Suriadi, Suriadi; Dewi, Eka Ratna (Jurnal Indonesia Sosial Sains, 2025)
Diabetes mellitus (DM) is a chronic disease with rising global prevalence, posing significant morbidity and mortality challenges. Skilled nurses play a pivotal role in DM management through holistic care, yet disparities in nursing knowledge, self-management practices, and resource limitations hinder optimal outcomes. This scoping review aims to map proficient nursing practices in DM care, identify barriers to effective self-management, and evaluate the impact of nurse-led interventions on patient outcomes. A systematic search was conducted on PubMed, Scopus, and Google Scholar (2015–2025) using keywords like "skilled nursing practice" and "diabetes mellitus." From 325 identified articles, 20 met inclusion criteria and were analyzed thematically. Key findings revealed: (1) a strong correlation between nurses’ knowledge/attitudes and quality of care; (2) socioeconomic and educational barriers to patient self-management; and (3) the cost-effectiveness and efficacy of nurse-led interventions in improving glycemic control (e.g., reduced HbA1c levels) and patient satisfaction. The study underscores the need for standardized nursing training, enhanced patient education, and policy support to address workforce shortages. By bridging knowledge gaps and optimizing nurse-led models, this review contributes to global DM care standards, advocating for scalable, patient-centered interventions.